Determine d , given that the real numbers a , b , c , and d satisfy
a 2 + b 2 + c 2 + 1 = d + a + b + c − d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Probably the most elementary solution Good
Writing this as a quadratic equation in d gives the discriminant 4 a − 4 a 2 + 4 b − 4 b 2 + 4 c − 4 c 2 − 3 . Now the maximal value of x − x 2 is 4 1 , attained at x = 2 1 . Thus the discriminant is nonnegative only when a = b = c = 2 1 , in which case we find d = 4 5
Nice solution! An essentially equivalent solution comes by substituting x 2 = a + b + c − d , giving a 2 + b 2 + c 2 + 1 = a + b + c − x 2 + x . By Completing The Square , this becomes ( a − 0 . 5 ) 2 + ( b − 0 . 5 ) 2 + ( c − 0 . 5 ) 2 + ( x − 0 . 5 ) 2 = 0 , so a = b = c = x = 0 . 5 , giving d = 1 . 2 5 .
Log in to reply
Yes, the solutions are mathematically equivalent, but the introduction of the variable x makes your solution more transparent.
Nice method
Brilliant :)
Sir can u plse elaborate? I could not understand your solution..@Otto Bretscher..
Log in to reply
Subtract d from the given equation and square to obtain a quadratic equation in d . The discriminant of this equation must be non-negative since we want d to be real.
Conversion obtained:
d = a^2 + b^2 + c^2 + 1/2 +/- Sqrt (a + b+ c - a^2 - b^2 - c^2 - 3/4)
Since not easy to get real d with discriminant < 0 usually, let x = a = b = c:
Discriminant = - 3 x^2 + 3 x - 3/4 = -3 (x - 1/2)^2
With x = 1/2 such that a = b = c = 1/2, Discriminant = 0 as an only hope.
d = 3 (1/2)^2 + 1/2 + 0 = 1.25
a 2 + b 2 + c 2 + 1 = d + a + b + c − d
I thought that writing d as " a + b + c + something " would make the square root much friendlier. Then I thought, writing it as " a + b + c - something " would make it even more friendlier. So :
Let d = a + b + c − f ( a , b , c , d )
I then noticed that substituting the other d as well would lead to a very nice surprise. Indeed:
a 2 + b 2 + c 2 + 1 = a + b + c − f ( a , b , c , d ) + f ( a , b , c , d )
can be rewritten as :
( f ( a , b , c , d ) − f ( a , b , c , d ) + 4 1 ) + ( a 2 − a + 4 1 ) + ( b 2 − b + 4 1 ) + ( c 2 − c + 4 1 ) = 0
In other words :
( f ( a , b , c , d ) − 2 1 ) 2 + ( a − 2 1 ) 2 + ( b − 2 1 ) 2 + ( c − 2 1 ) 2 = 0 (constantly hunting for factorisations made it easier to see this idea)
Thus we obtain : f ( a , b , c , d ) = a = b = c = 2 1 .
And finally d = 4 5 = 1 . 2 5
Let C1 = a^2 + b^2 + c^2 + 1, C2 = a + b + c, u = sqrt(C2 - d) Equation will become system: C1 - d = u and C2 - d = u^2 => u^2 - u = C2 - C1 Delta of above equation is del = 1 + 4C2 - C1 = -(2a - 1)^2 - (2b-1)^2 - (2c-1)^2 <=0 Therefore, a = b = c = 1/2 => C1 = 7/4 Moreover, u will have only 1 root and it's u = 1/2 Thus, d = C1 - u = 5/4
a=b=c=1/2,Therefore L.H.S= a+b+c+1=1/4+1/4+1/4+4/4 =7/4 and R.H.S = 5/4+ root of2/4+2/4+2/4-5/4=5/4+root of 1/4 ie 5/4+1/2=5/4+2/4 = 7/4 Hence LHS=RHS= 1.25
Problem Loading...
Note Loading...
Set Loading...
a 2 + b 2 + c 2 + 1 = d + a + b + c − d
add a + b + c to both sides and take d and a + b + c − d to the left
a 2 + b 2 + c 2 + ( a + b + c − d ) − a + b + c − d + 1 = a + b + c
now take 4 1 out of the 1 and we can rewrite the equation as
a 2 + b 2 + c 2 + ( a + b + c − d − 2 1 ) 2 + + 4 3 = a + b + c
on further rearrangement we get
( a 2 − a + 4 1 ) + ( b 2 − b + 4 1 ) + ( c 2 − c + 4 1 ) + ( a + b + c − d − 2 1 ) 2 = 0
or
( a − 2 1 ) 2 + ( b − 2 1 ) 2 + ( c − 2 1 ) 2 + ( a + b + c − d − 2 1 ) 2 = 0
⇒ a = b = c = 2 1 and d = 4 5